2018
DOI: 10.1080/14737140.2018.1489245
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated radiation treatment in the management of breast cancer

Abstract: The standard treatment for early-stage breast cancer is breast conservation therapy, consisting of breast conserving surgery followed by adjuvant radiation treatment (RT). Conventionally-fractionated whole breast irradiation (CF-WBI) has been the standard RT regimen, but recently shorter courses of hypofractionated whole breast irradiation (HF-WBI) have been advocated for patient convenience and reduction in healthcare costs and resources. Areas covered: This review covers the major randomized European and Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 78 publications
3
17
1
Order By: Relevance
“…In this study, BC patients enrolled in the study in southern China all underwent surgery, and the treatment including BCS and mastectomy (including SM and MRM). Among them, there were about 95.09% of BC patients performed mastectomy and 4.91% of that performed BCS, and the implementation rate of BCS was signi cantly lower than that of developed countries, which was similar to the results of Gupta A: the highest implementation rate of BCS in China is only 8.6% [48] . However, there were only 18.24% of BC patients performed mastectomy in SEER cohort, 81.76% of that had not.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In this study, BC patients enrolled in the study in southern China all underwent surgery, and the treatment including BCS and mastectomy (including SM and MRM). Among them, there were about 95.09% of BC patients performed mastectomy and 4.91% of that performed BCS, and the implementation rate of BCS was signi cantly lower than that of developed countries, which was similar to the results of Gupta A: the highest implementation rate of BCS in China is only 8.6% [48] . However, there were only 18.24% of BC patients performed mastectomy in SEER cohort, 81.76% of that had not.…”
Section: Discussionsupporting
confidence: 76%
“…But for SEER cohort had not include the details of surgical procedures, so its' effects on survival and prognosis of BC were not studied and analyzed, which may be a potential factor. In recent years, a number of large randomized trials have shown that radiotherapy could signi cantly reduce the local recurrence of BC, so as to improve the breast preservation rate and obtain good survival rate [48]. However, in this study, the radiotherapy rate of BC patients in southern China and SEER cohort were both not high, were 27.18% and 34.22% respectively, and there were signi cant statistical different between the two (P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Hypofractionation at a dose of 40/15 or 42.5/16 is the standard of care after breast conservative surgery. 14 However, the use of hypofractionation for locoregional treatment as well as in the setting of PMRT with or without immediate reconstruction is controversial. 7 The Danish and Canadian postmastectomy landmark trials that revealed survival advantage following the addition of adjuvant radiation after mastectomy have actually delivered hypofractionated regimens.. 15,16 In the United Kingdom (UK), it is standard practice to offer hypofractionated radiotherapy to all patients in the adjuvant setting.…”
Section: Results Characteristics Of the Survey Participantsmentioning
confidence: 99%
“…The article published in Cancer Radiotherapy by Parisi and colleagues went one-step further and demonstrated the safety of hypofractionated hemithoracic radiation after PD in MPM using 25 Gy in 5 fractions (2). Hypofractionated rather than normofractionated radiation has been used in the adjuvant setting (for instance after surgery for breast cancer) to improve quality of life at less cost since a biologically equivalent dose of radiation can be reached in a shorter period of time (22). In the retrospective study from Parisi and colleagues, the rate of grade 1 pneumonitis was 97% in the acute phase and 47% in the late phase after radiation (2).…”
mentioning
confidence: 99%